2015
DOI: 10.1038/eye.2015.187
|View full text |Cite
|
Sign up to set email alerts
|

‘Shadow sign’ in congenital hypertrophy of the retinal pigment epithelium of young myopic pigmented patients

Abstract: Purpose Congenital hypertrophy of the retinal pigment epithelium (CHRPE) may simulate choroidal melanoma in certain cases. We report unique clinical features we have observed in cases of CHRPE in young myopic pigmented patients. Methods Patients who were referred for evaluation of a suspicious choroidal lesion and found to have a CHRPE lesion with the clinical appearance of lesion elevation and a subretinal fluid-like 'shadow sign' were included. Patient and lesion characteristics were tabulated. Available ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
3
9
1
Order By: Relevance
“…Upon review of the literature, dark without pressure findings were either isolated or found co-existing with other ocular pathologies including sickle cell retinopathy, myopia, congenital hypertrophy of the RPE, and astrocytic hamartoma. 3,4,8,9 To our knowledge, no previous case of dark without pressure associated with or coinciding with choroidal osteoma has been reported. It is important to note that this adjacent finding was not a reactive hyperplastic response to the choroidal tumor as evidenced from the peripheral OCT showing the characteristic outer retinal changes in reflectivity of dark without pressure lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Upon review of the literature, dark without pressure findings were either isolated or found co-existing with other ocular pathologies including sickle cell retinopathy, myopia, congenital hypertrophy of the RPE, and astrocytic hamartoma. 3,4,8,9 To our knowledge, no previous case of dark without pressure associated with or coinciding with choroidal osteoma has been reported. It is important to note that this adjacent finding was not a reactive hyperplastic response to the choroidal tumor as evidenced from the peripheral OCT showing the characteristic outer retinal changes in reflectivity of dark without pressure lesions.…”
Section: Discussionmentioning
confidence: 94%
“…The existence of DWOP lesions has been reported in several diseases, but the incidence rate of DWOP lesions has rarely been reported [ 22 , 23 , 24 ]. In the case series reported by Fawzi A et al [ 7 ] DWOP was found in a 25-year-old girl with myopia and showed no significant progress at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Amani A. Fawzi [ 7 ], WWOP was shown to have no relation to vitreal-retinal traction, but was related to the reflectivity changes in the photoreceptor layer, which is consistent with our research (shown in Figure 1 ). Previous studies have shown that DWOP can be seen in many fundus diseases, including hemoglobinopathy [ 15 ], retinal astrocytoma [ 7 ], white dot syndrome [ 7 ], HLA-B27 anterior middle uveitis [ 7 ], congenital retinal pigment epithelial hypertrophy [ 7 , 22 ], AIDS [ 19 ], Ebola [ 23 ], and choroidal osteoma [ 24 ]. The common feature of DWOP in OCT images is that the EZ is faded or has disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…They highlighted the familiarity of this phenomenon with the OCT appearance of the dark adapted Mizuo-Nakamura-phenomenon, but had discrepancies, especially the circumscribed character of the photoreceptor abnormalities, normal full-field electroretinogram and the absence of functional deficits in DWP. Li, et al [6] and Chang, et al [7] reported about cases presenting with DWP, surrounding or near a congenital hypertrophy of the retinal pigment epithelium (CHRPE) area. As CHRPE have been associated to WWP [8], Chang, et al [7] suggested a possible induction of alteration of the vitreoretinal surface by the CHRPE, although in their case-series, the OCT showed no vitreoretinal alteration.…”
Section: Case Presentationmentioning
confidence: 99%
“…Li, et al [6] and Chang, et al [7] reported about cases presenting with DWP, surrounding or near a congenital hypertrophy of the retinal pigment epithelium (CHRPE) area. As CHRPE have been associated to WWP [8], Chang, et al [7] suggested a possible induction of alteration of the vitreoretinal surface by the CHRPE, although in their case-series, the OCT showed no vitreoretinal alteration. Steptoe, et al [9] reported having identified DWP next to 88.7% of the lesions due to Ebola virus disease in their patient cohort.…”
Section: Case Presentationmentioning
confidence: 99%